A New Gradient Based Surface Defect Detection Method for the Ceramic Tile - Murat Alparslan Güngör (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Ceramic tiles are controlled to detect surface defects after production because many defects may occur on their surface during production. The detection of ceramic tile surface defects is usually performed by human observations in most factories. In this paper, an image processing method was proposed to detect the defects. In the proposed method, first, the user selects the homogenous region in the image. Then the gradient-based image processing algorithm is applied. We conducted our study using simulated and real images to which we applied the conventional image processing methods and our proposed method. Performance of the proposed method was evaluated with quality metric and subjective evaluation. The obtained results demonstrate that the proposed method has very good performance and is very promising for ceramic tile application.